The Most Common Injuries in Soccer: An Analytical Review - Dąda, Paweł; Pawlik, Paweł; Zaroda, Przemysław (Quality in Sport, 2024)
Soccer, also known as football in many parts of the world, is a sport with a high incidence of injuries due to its physically demanding nature. This paper reviews the most common injuries sustained by soccer players, their causes, prevention strategies, and rehabilitation processes. Understanding these injuries can help in developing better training programs and safety measures to protect athletes.